Jogos educativos: brincando, ensinando e aprendendo matemática no ensino fundamental - Rocha, Demóclis do Carmo (2018)
This dissertation is about the use of educational games to flourish curiosity and interest among students in basic education. The Group Memory Game and the Participation Game araised from daily lessons with my students from Bárbara de Alencar School. The Tangram and the Tower of Hanoi are very well known games that are also discussed in this dissertation. An experimentation with Algeplan is also presented. I named Subtraction Game the use of basic concepts of Number Theory that make the learning of subtraction algorithm and the divisibility rule of nine more interesting for students.